Small Conductive Particle Detection with a Microwave Resonant Cavity. Issue 2 (24th October 2013) - Ikeda, Makoto; Mase, Atsushi; Uchino, Kiichiro
SUMMARY The recent miniaturization and increased complexity of electrical devices have increased the influence of impurities on device performance, especially the influence of small conductive particles with a size on the order of micrometers. Therefore, the inspection of devices during the manufacturing process has become important. In this study, changes in the resonance properties of a microwave cavity were used to detect a metal particle. The decrease in the resonant frequency for a 100‐µm stainless steel sphere was about 0.1 MHz, which was less than 1 ppm of the resonant frequency used. This frequency change is too small to detect directly in the output of a particle detector. Transmission measurements (the scattering parameter S21) at a frequency that was a few megahertz higher than the resonant frequency where the S21 changes sharply were used to magnify signal changes resulting from the introduction of a small conductive particle. A resonant frequency of 13.3 GHz and a frequency 3 MHz higher were chosen for obtaining measurements in the present study. By applying a filtering technique, it was shown that the minimum detectable sphere size is around 50 µm. This sensitivity was experimentally shown to be uneven along the long axis of the cavity. The unevenness was related to the electrical field strength of the standing wave at the resonant frequency. For practical industrial inspection of devices, multiple frequencies should be employed in view of the present discussion. © 2013 Wiley Periodicals, Inc. Electr Eng Jpn, 186(2): 61–67, 2014; Published online in Wiley Online Library (wileyonlinelibrary.com). DOI 10.1002/eej.22490